2017
DOI: 10.1128/iai.00195-17
|View full text |Cite
|
Sign up to set email alerts
|

RNA Interference Screening Reveals Host CaMK4 as a Regulator of Cryptococcal Uptake and Pathogenesis

Abstract: Cryptococcus neoformans, the causative agent of cryptococcosis, is an opportunistic fungal pathogen that kills over 200,000 individuals annually. This yeast may grow freely in body fluids, but it also flourishes within host cells. Despite extensive research on cryptococcal pathogenesis, host genes involved in the initial engulfment of fungi and subsequent stages of infection are woefully understudied. To address this issue, we combined short interfering RNA silencing and a high-throughput imaging assay to iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Tissue culture medium was chosen as a “host-like” condition that resembles the context under which C. neoformans would be most likely to experience oxidative stress (26). Morphology was categorized as diffuse, where the mitochondria are distributed in a thin, reticular network without strong focal regions of fluorescence; fragmented, where the dominant impression is of individual puncta scattered throughout the cell; or tubular, where large fused tubules may be observed (see Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tissue culture medium was chosen as a “host-like” condition that resembles the context under which C. neoformans would be most likely to experience oxidative stress (26). Morphology was categorized as diffuse, where the mitochondria are distributed in a thin, reticular network without strong focal regions of fluorescence; fragmented, where the dominant impression is of individual puncta scattered throughout the cell; or tubular, where large fused tubules may be observed (see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In parallel, cryptococcal strains were grown overnight in YPD and washed as above, opsonized in 40% human serum in PBS (30 min at 37°C at 1 × 10 7 cells/ml), washed in PBS, and resuspended in prewarmed (37°C) RPMI. Opsonized fungi were added to differentiated THP-1 cells at an MOI of 0.1 in triplicate wells in three parallel plates (26, 56). The plates were incubated for 1 h to permit uptake of opsonized cells, washed twice with sterile prewarmed PBS, and refilled with prewarmed THP-1 medium.…”
Section: Methodsmentioning
confidence: 99%
“…In one example, Chun and colleagues subjected cryptococcal cells to insertional mutagenesis and identified mutations that affected their uptake by RAW264.7 macrophages (18). Srikanta et al used RNA interference and high-throughput imaging to find host regulatory genes which govern the interactions of C. neoformans with THP-1 cells and discovered 25 fungal-specific regulators of phagocytosis (19). By applying a similar high-throughput imaging assay to a C. neoformans gene deletion collection (20), Santiago-Tirado et al identified 56 fungal genes that affect uptake by THP-1 cells (10).…”
Section: Introductionmentioning
confidence: 99%
“…The method presented here allows quantitation of the initial engulfment of C. neoformans. By using an automated assay to measure phagocytosis (Srikanta, Yang, Williams, & Doering, 2011), we can efficiently study fungal (Santiago-Tirado, Peng, Yang, Hang, & Doering, 2015), host (Srikanta, Hole, Williams, Khader, & Doering, 2017), or environmental factors that influence the avidity of uptake.…”
Section: Introductionmentioning
confidence: 99%